Herpetofauna Assemblages And Microhabitat Assessment At Royal Belum State Park, Perak - Tan, Siew Heng (2019)
Amphibians and reptiles, known collectively as herpetofauna, are significant components of various ecosystems. Due to their important roles in the ecosystem, herpetofauna around the world is now the focus of scrutiny as their populations continue to decline due to increased pollution, habitat destruction and climate change. While most of the herpetofaunal studies conducted were mainly on their biodiversity, there are only a handful of studies that emphasise on the microhabitat and macroclimate requirements of herpetofauna especially in Malaysia. This study focused on the biodiversity, microhabitat and macroclimate preferences of herpetofauna in Royal Belum State Park that is now threatened with increased ecotourism, harvesting and poaching activities. The biodiversity of herpetofauna was investigated using Drift-fenced Pitfall Traps in conjuction with Visual Encounter Survey (VES) throughout a 12 month-sampling period. The study successfully documented a total of 38 species with 199 individuals that came from 6 families of amphibians and 8 families of reptiles from the three sampling sites in Royal Belum State Park. Although species new to science was not discovered in this study, but five new records were documented for the whole Belum-Temengor Forest Complex, bringing the total number of amphibians and reptiles to 42 and 73 respectively. Among the 38 species, Ingerophrynus parvus from the Order Anura was the most abundant amphibian species whereas Eutropis multifasciata from the Order Squamata was the most abundant reptile species. Heosemys spinosa was the only species found for the Order Testudines.